THE USE SKIN STARCH OF JACKFRUIT (Artocarpus heterophyllus) AND CHITOSAN IN A BIOPLASTIC PRODUCTION WITH THE ADDITION OF VIRGIN COCONUT OIL (VCO) AS PLASTICIZER - Hamsina Hamsina; Indra Jaya; Nani Anggraini; Andi Tenri Fitriyah; Ruslan Hasani (Jurnal Industri Hasil Perkebunan, 2022)
This study aims to determine the best concentration on the comparison of jackfruit skin starch and chitosan with the addition of virgin coconut oil (VCO) as a plasticizer and the characteristics of bioplastics. The research method consisted of the following steps: extracting jackfruit skin starch using two processes, namely the delignification process and the bleaching process. The production of bioplastics was carried out with the following treatments: Jackfruit skin starch: chitosan, each with a ratio of P1= 100%:0%; P2 = 85%:15%; P3 = 70%:30% and P4 = 55%:45% with the addition of VCO of 10% of the total starch of jackfruit skin and chitosan and stirred for 1 hour until homogeneous. The resulting solution was then printed on a glass mold with a size of 20 x 15 cm and dried in an oven at 60oC for 6 hours. The bioplastics were cooled at room temperature for 6 hours then removed from the glass plate and stabilized in a desiccator before being analyzed. Data analysis used the Completely Randomized Design (CRD) method with 4 treatment levels and three replications. The results showed that the addition of chitosan and VCO had a very significant effect (p<0.05) on the characteristics of bioplastics. The best treatment ratio was obtained in the ratio of jackfruit skin starch: chitosan 55%:45% with each thickness value of 0.1682 mm, tensile strength of 0.5933 MPA, 20% water absorption and 50% biodegradability test which can be degraded for 3 weeks.